Hubungan Antara Audit Internal Dan Kualitas Laporan Keuangan Di SMKN 1 Surabya - Sofi Yulia Rakhmawati (Universitas 45 Surabaya, 2023)
This study aims to analyze the relationship between internal audit and the quality of financial reporting at SMKN 1 Surabaya. Data collection was carried out through interviews with relevant parties in the school, such as the school finance sub-section. Data analysis was carried out using a qualitative descriptive analysis technique, in which the results of the interviews were analyzed and interpreted to understand the relationship between internal audit and the quality of financial reporting at SMKN 1 Surabaya. Internal audit plays an important role in improving the quality of financial reports because internal audit plays an important role in checking financial and accounting activities carried out internally in an organization. Internal audit helps ensure that information on financial and accounting activities in schools is carried out correctly and in accordance with applicable rules and regulations. In the context of schools, the quality of financial reporting is very important because schools are public educational institutions that are funded by the government and the general public. Internal audits at SMKN 1 Surabaya are carried out regularly to control all school activity programs, identify problems that occur, check financial reports, and provide recommendations for improvement. The results of the study show that internal audit contributes positively to the quality of financial reporting at SMKN 1 Surabaya.